EP 3. Nigral stimulation for freezing of gait: Clinico-anatomic correlations. Issue 9 (September 2016) - Hanci, I.; Scholten, M.; Roncoroni, L.P.; Krueger, R.; Gharabaghi, A.; Weiss, D.
Abstract : Objective: In this study we aimed to address the impact of electrode localization in idiopathic Parkinson's disease patients (iPD) with combined stimulation of the subthalamic nucleus (STN) and substantia nigra pars reticulate (SNr) and freezing of gait (FOG). Background: FOG presents as disabling and often resistant motor symptom in iPD. First evidence for an effect of additive SNr stimulation on otherwise resistant FOG came from a recent randomized controlled trial (Weiss et al., 2013 ) and translates now into a multicenter German-wide trial. Methods: Ten patients with advanced iPD and combined STN + SNr stimulation were followed over a period of 12 months with regular visits at start (STN stimulation) as derived from the standard STN scores of our cross-over study (Weiss et al., 2013), and 6 week (STN+SNr stimulation) and 12 month (STN + SNr stimulation) follow-up as derived from our observation open-label study. MCP based coordinates of active SNr contacts were determined with Medtronic Optivise TM system and FOG was assessed by the Freezing Assessment Course (FAC). The difference of the FAC-score between 6 weeks STN+SNr to STN and 12 months STN + SNr to STN stimulation were built. The coordinates of active SNr contacts were correlated with therapeutic effects of combined STN+SNr stimulation on FAC. Results: Improvement of FOG with combined STN+SNr stimulation was correlated with more medial positions of the left active SNr contact at six week follow-up. The left SNr contact was located more medially in strong responders (<50% improvement in FAC) ( n = 5) compared to mild or non-responders (FAC improvement <50%) ( n = 5) at six week ( n = 10). There was no correlation of electrode laterality and FOG impairment with STN stimulation excluding confounding of our findings by stratification. No correlation of electrode position and FOG improvement was identified at 12 months ( n = 8, two drop-outs). Conclusion: The results may point to superior treatment effects if the active SNr electrode is placed more medially. However, the findings have to be considered with caution and unilateral clinical test stimulations and correlations with the clinical effect on FOG have to give closer insight in future.